2022
DOI: 10.9745/ghsp-d-21-00664
|View full text |Cite
|
Sign up to set email alerts
|

Human-Centered Design for Public Health Innovation: Codesigning a Multicomponent Intervention to Support Youth Across the HIV Care Continuum in Mozambique

Abstract: Using human-centered design (HCD), key learnings identified opportunities for intervention to promote viral suppression and improve ART adherence and retention in care among adolescents and young people living with HIV (AYAHIV). Opportunities included fostering a sense of belonging and peer connectedness with other AYAHIV, providing contextually resonant medical knowledge that fits the unique context of adolescence and young adulthood, reducing misconceptions and stigma surrounding HIV, and cultivating a sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Although mixed methods will deliver in-depth qualitative understanding of patient choices, DCEs will allow stakeholders to weigh different cure intervention characteristics, make trade-offs and select appropriate options [ 58 , 59 ▪ ]. The HCD borrowed from economics and gaining grounds in healthcare and HIV research is an iterative process that narrows the gap between an intervention being planned and end user preferences [ 60 , 61 ▪▪ , 62 ]. Thus, bringing together scientists working on HIV cure, patients, ethicists, economists and socio-behavioural scientists could yield new ideas that can feed into the design of cure interventions, and early termination of approaches that are likely to be rejected by patients and caregivers.…”
Section: Advancing the Acceptability Cure Agendamentioning
confidence: 99%
“…Although mixed methods will deliver in-depth qualitative understanding of patient choices, DCEs will allow stakeholders to weigh different cure intervention characteristics, make trade-offs and select appropriate options [ 58 , 59 ▪ ]. The HCD borrowed from economics and gaining grounds in healthcare and HIV research is an iterative process that narrows the gap between an intervention being planned and end user preferences [ 60 , 61 ▪▪ , 62 ]. Thus, bringing together scientists working on HIV cure, patients, ethicists, economists and socio-behavioural scientists could yield new ideas that can feed into the design of cure interventions, and early termination of approaches that are likely to be rejected by patients and caregivers.…”
Section: Advancing the Acceptability Cure Agendamentioning
confidence: 99%
“…Human-centered Design (HCD) is an approach that aims to engage diverse stakeholders in exploring needs and creating people-focused solutions that consider individual experiences, motivations, beliefs, and desires [ 24 – 27 ]. Praised for its ability to facilitate the development of culturally relevant and practical solutions, HCD also increases the likelihood of community uptake and program sustainability [ 24 , 28 ]. It offers participatory and creative tools to facilitate the design process with users and is flexible and iterative [ 29 ], which allows for the approach to be applied differently depending on the context and key challenges.…”
Section: Introductionmentioning
confidence: 99%
“…However, HCD is on the rise in public and global health, where it has been used to define community problems, design interventions, evaluate program impacts, increase the usability of health solutions, and more [ 29 , 30 , 31 ]. In fact, numerous studies have found that HCD is particularly well-suited to address global health challenges [ 28 , 32 35 ]. Teams across several regions and continents have utilized HCD to tackle diverse health-related issues, such as enhancing HIV care, addressing noncommunicable diseases, and combating violence against women [ 28 , 33 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a multistep, iterative process, HCD gathers perspectives and experiences from key stakeholders and end users for intervention development and adaptation with a particular strength in technology integration (Lyon et al, 2019): a collaborative approach between researchers and users to create a more viable, usable final product that aligns with the preferences of the study populations (Beres et al, 2019; Harte et al, 2017). Although used to adapt and develop multiple mHealth and in-person interventions for HIV prevention and education globally (Mukherjee et al, 2022), HCD is only emerging as a framework in African contexts despite the well-established community-driven HIV response, IT infrastructure, and smartphone usage (Beres et al, 2019). A few studies using HCD have worked with both patients and providers to improve HIV outcomes across African settings.…”
Section: Introductionmentioning
confidence: 99%